Dental visits among adolescents in Brazil: descriptive analysis of the National School Health Survey, 2019 - Hellen Monique da Motta; Nathalia Ribeiro Jorge da Silva-Garcia; Letícia Regina Morello Sartori; Maria Beatriz Junqueira de Camargo; Sarah Arangurem Karam (Epidemiologia e Serviços de Saúde)
Abstract Objective To describe the prevalence of dental visits among adolescents participating in the 2019 National School Health Survey (PeNSE). Methods A descriptive cross-sectional study analyzing dental visits in the last year considering sex, race/skin color, maternal education and dental pain. Only PeNSE 2019 participants between ages 13 and 15 years were included. Absolute and relative frequencies were verified using Pearson’s Chi-square test, with a 5% confidence level (p-value<0.05) and the respective 95% confidence intervals (95%CI). As a secondary analysis, data on dental coverage in primary health care were collected and reported according to Brazilian regions. Results The prevalence of visits to the dentist in the last year was 66.7%; a higher prevalence was noted for adolescents who declared themselves white compared to black adolescents (71.8% versus 61.9%), for females (68.4%; 95%CI 67.27; 69.49), among students with toothache (69.4%; 95%CI 67.61; 71.10) and with mothers with higher education (77.9%; 95%CI 76.56; 79.18). Federative units with high dental coverage reported lower use of services, while those with lower coverage reported a higher proportion of visits to the dentist. Conclusion Among adolescents aged 13 to 15 years, a 66.7% prevalence of visits to the dentist in the last year was observed; higher prevalences of visits to the dentist were found among female adolescents, self-declared white, with mothers with higher education and with self-reported toothache. Furthermore, there was a lower prevalence of visits to the dentist in places with greater dental coverage.